SOLUSI PENCAPAIAN BIAYA MINIMUM BAGI PASANGAN LIMA PEKERJAAN DAN LIMA MESIN MENGGUNAKAN METODE HUNGARIAN - Liana, Lie; Susilowati, Yeye; Suhana, Suhana (Proceeding SENDI_U, 2017)
In daily life a human often does a work with a machine. Commonly a work can be accomplished by many machines. Conversely one machine can finish many works. Tasking model is a special form of linear programming used to seek the most efficient task to determine whether a work can be accomplished by which machine. The main goal of tasking model is to find work and machine pairs in such a way that it can minimize total cost.Main characteristic of tasking model is a machine is focused for a work and conversely a work is only finished with one machine. The term for such condition is one to one correspondence or one to one basis so the number of employees must be the same with number of machine. The problem is how to pair five works with five machines in such a way to minimize cost. Though linear programming can be used to gain optimum solution of work and machine, a more efficient algorith has been developed to accomplish the problem. The method is called Hungarian method.By using Method of Hungarian, it is derived work and machine pairs in such a way so that minimum cost can be gained amounted 1.700.000.000,-. Keywords: model of tasking, one to one basis, method of Hungarian